Two new earthworm species of the genus Metaphire Sims & Easton, 1972 (Annelida: Oligochaeta: Megascolecidae) from Highlands of Vietnam - Phan, Quoc T.; Lam, Dang H.; Tran, Men T.; Pham, Quang V.; Nguyen, Anh D. (Zootaxa, 2026)
Two new earthworm Metaphire species are described from Highlands of Vietnam, namely Metaphire mangcanhensis sp. nov. and Metaphire dalatensis sp. nov. The former belonging to M. merabahensis species-group, is characterized by three pairs of spermathecal pores in 5/6/7/8, first dorsal pore at 12/13, a pair of three genital markings clustered in vii, and simple intestinal caeca while the latter belonging to M. houlleti species-group, is distinguished by first dorsal pore at 10/11, male pore distance about 0.33 body circumference, ampulla duct distally enlarged, and lacking penial setae. The COI barcodes are also provided for both species.